Perhitungan Kebutuhan Air Bersih dan Perencanaan Kebutuhan Infrastruktur Perpipaan PDAM di Kel Sako, Sako Baru, Sialang dan Sukamaju Kec. Sako Kota Palembang - Delli Noviarti Rachman; Susi Riwayati (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
The service of clean water in urban areas is very important to be given special attention. PDAM Tirta Musi The Sako Kenten Service Unit serves 4 sub-districts in Sako sub-district, including Sako, Sako Baru, Sialang, and Sukamaju. As the area grows, the population also increases. It is estimated that in 2029 the total population in Sako sub-district will reach 106,273 people. Meanwhile, for now the population which only reaches 93,326 people, it is felt that there is a shortage of clean water supply from PDAM. Based on the results of surveys and interviews, information was obtained that the availability of clean water from PDAM in the Sako area is only 6,000 liters per month on average. This is not enough for the population. It becomes a big task for PDAM Tirta Musi to prepare it by building an adequate pipeline network. Another problem is the existing piping system does not support the flow with such a large discharge, so it requires a network using the latest material, namely using HDPE pipes. The use of this material was chosen because HDPE does not require much connection and the pipe is stronger than PVC pipe. After carrying out the survey and calculation of the RAB, it was found that the need for a new network system reached Rp. 53,756,600,000, - in order to meet service standards for 80% of the population in Sako District. Keywords : PDAM Tirta Musi, Projection of water demand, Pipeline Network Budget Plan